The Strategic Role and Implementation of the Sustainable Development Goals through Public Libraries: A Multi-Case Study in Seven Provinces with the Highest Regional Competiveness Index (RCI/IDSD) Scores in Indonesia - Anita Tri Widiyawati; Kanyarat Kwiecien; Lan Thi Nguyen (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
Public libraries have become important organizations in fostering and stimulating inclusive and sustainable development in contemporary knowledge societies. This research adopted an integrated mixed-methods approach by examining the role of public libraries in Indonesia in supporting the implementation of the Sustainable Development Goals (SDGs). The qualitative research showed that libraries were inclusive knowledge organizations that connect the global development and the local community through policy alignment, digital transformation, and multistakeholder cooperation. Libraries fostered development of literacies and encourage social inclusion, ensure cultural preservation and boost community empowerment, although some issues remain, like inadequate resources, technological inequality and uneven institutional capacity. The measurement model yielded strong and valid constructs for the key dimensions of the initiative, namely administration, staff, training, resources, infrastructure, partnerships, and SDG outcomes (People, Planet, Prosperity and Peace), shown by standardized estimates which were all significant. The findings established that successful implementation of SDGs by libraries hinges upon the quality of governance, collaborative networks, and adaptive delivery of services. The research revealed that public libraries become strategic actors in the field of inclusive and sustainable development, especially at the local level. Stronger institutional and digital capacities, along with better-integrated planning, are needed to optimize the contribution of libraries to the SDG, it was pointed out.